Disability in Restorative Proctocolectomy Recipients Measured using the Inflammatory Bowel Disease Disability Index. (9th June 2016) - Lee, Y.; McCombie, A.; Gearry, R.; Frizelle, F. A.; Vanamala, R.; Leong, R. W.; Eglinton, T.
Abstract: Background and Aims: The inflammatory bowel disease [IBD] disability index [IBD-DI], which measures IBD-associated disability, has been validated on IBD patients but not those who have had restorative proctocolectomy with ileal pouch-anal anastomosis [RP with IPAA]. This study aimed to utilize the IBD-DI in RP with IPAA recipients and compare ulcerative colitis [UC]-indicated RP with IPAA patients to medically treated UC patients. Methods: This study was population based. Demographic, indication, complication and direct cost data were collected via medical records while disability, quality of life [QoL] and indirect costs were measured using questionnaires and structured interviews. De-identified raw data about medically treated UC patients were provided by a previous study for comparison. Results: In total there were 136 RP with IPAA patients [mean 11.5 years of follow up]. Eighty-four completed the IBD-DI and 80 completed the IBD questionnaire [IBDQ]. The IBDQ and IBD-DI were highly correlated [ r = 0.84, p < 0.01]. Worse QoL and disability were found in those who had their position affected at work [both p < 0.01] and those who had more than 100 days off work in the last year [ p < 0.01 for QoL and p = 0.012 for disability]. Lower QoL and disability scores were associated with higher indirect and total costs [ p < 0.01]. UC patients treated with RP with IPAA had less disability than medically treated UC patients [ p = 0.04]. Conclusions: Disability in RP with IPAA recipients can be measured using the IBD-DI. Perioperative complications and high costs of care are associated with higher levels of disability. Disability of RP with IPAA recipients was lower than that of medically managed UC patients.